Chemoselective N-Nitrosation of Secondary Amines under Mild and Heterogeneous Conditions with ZrCl4/NaNO2 - Ali Zolfigol, Mohammad; Shirni, Farhad; Ghorbani Choghamarani, Arash; Shiri, Aazam; Keypour, Hassan; Salehzadeh, Sadegh (Asian Journal of Chemistry, 2010)
A combination of zirconium tetrachloride and sodium nitrite in the presence of wet SiO2 was used as an effective nitrosating agent for the nitrosation of secondary amines to their corresponding nitroso derivatives under mild and heterogeneous conditions in excellent yields.